Valorization of glass waste into glass powder in the manufacture of concrete - Merdaci, Slimane (Vojnotehnički glasnik / Military Technical Courier, 2025)
The valorization of waste in the field of civil engineering is significant because the products obtained are not subject to overly stringent quality criteria. Waste valorization has two major impacts: environmental and economic. In many countries around the world, various types of waste are used in construction, especially in cement or concrete, as powders, fibers, or aggregates. This work focuses on valorizing an environmentally harmful waste: glass waste. Different types of glass waste are added to concrete by replacing a certain amount of sand in varying percentages. The various concretes produced are analyzed and compared to their respective control concretes to assess the feasibility of incorporating glass into the construction sector.
Keywords: Glass powder; Concrete; Substitution; Mechanical properties.; Valorization